Examination of food reward and energy intake under laboratory and free-living conditions in a trait binge eating subtype of obesity - Dalton, Michelle; Blundell, John; Finlayson, Graham S. (Frontiers in Psychology, 2013)
Background/Aims: Trait binge eating has been proposed as a “hedonic subtype” of obesity characterized by enhanced food liking and wanting, and a preference for high-fat sweet foods in the laboratory. The current study examined the influence of trait binge eating in overweight or obese women on eating behavior under laboratory and free-living conditions over a 48-h period. Methods: In a matched pairs design, 24 overweight or obese females (BMI: 30.30 ± 2.60 kg/m2; Age: 25.42 ± 3.65 years) with high or low scores on the Binge Eating Scale (BSE) were divided into one of two groups; Obese Binge (O-B) and Obese Non-binge (O-NB). Energy intake was assessed using combined laboratory energy intake measures and 24-h dietary recall procedures. Liking and wanting were assessed using the Leeds Food Preference Questionnaire (LFPQ). Results: There was a significant association between overall energy consumed, and energy consumed from snack foods under laboratory and free-living conditions. O-B exhibited a greater preference for sweet snack foods in their laboratory and free-living eating behavior. These findings were supported by greater laboratory-based measures of wanting and craving for this food type in O-B. In addition, O-B consumed significantly more energy than their estimated daily energy requirements in the laboratory suggesting that they over-consumed compared to O-NB. Conclusions: The measurement concordance between laboratory and free-living based energy intake supports the validity of laboratory-based test meal methodologies Variation in trait binge eating was associated with increased craving and wanting for high-fat sweet foods and overconsumption in the laboratory. These findings support the use of trait binge eating as a common hedonic subtype of obesity and extend the relevance of this subtype to habitual patterns of energy intake.